APPLYING TASK ANALYSIS TO DEVELOP THE NECESSARY SKILLS OF STUDENTS WITH MDVI: FOCUSING ON COOKING RICE USING THE ADAPTED RICE COOKER (Proceedings of International Conference on Special Education, 2017)
Independence plays an important role in the process of transition. In order to prepare the 5 students with MDVI in Grade 6 of Ban Dek Ramintra School for the Blind and Blind with Multiple Disabilities for transition, they have to undergo the preparation process at Half-way House for a period of one year. The Half-way House Project includes teaching daily living skills and vocational skills to students with MDVI. One of the daily living skills they learn through the Half-way House Project is cooking. Before conducting this study, 80% of Grade 6 students with MDVI of Half-way House Project at Ban Dek Ramintra School for the Blind and Blind with Multiple Disabilities were not able to cook rice all by themselves using the rice cooker. They lacked the necessary skills to perform this task. Rice is the staple food in Thailand. It is included at most meals of Thai people. Therefore, cooking rice is an important skill that students with MDVI need for their daily life. To ensure a scientific process in teaching the task of cooking rice, I included the application of task analysis, object identification techniques and Orientation and Mobility. I also devised an Individualized Instructional Plan (IIP) and used an adapted rice cooker with tactile buttons and audio signals modified by our visually impaired resident technician. The combination of techniques and the use of adapted rice cooker enabled the students with MDVI to understand clearly what to do to complete the task. With this new knowledge and skills, students with MDVI are able to perform a task that will not only benefit them but also other people. They can now cook rice for themselves and also for their friends and family. The mixed method of using task analysis, object identification techniques and O&M to complete the task will be used as an instructional model for other students with MDVI at Ban Dek Ramintra and other schools for students with MDVI under CFBT